Solvent Control in Electro-Organic Synthesis - Schulz, Lara; Waldvogel, Siegfried R. (Synlett, 2019)
Exploiting the solvent control within electro-organic conversions is a far underestimated parameter in prep-scale electrolysis. The beneficial application in several transformations is outlined and in particular discussed for the dehydrogenative coupling of arenes and heteroarenes. This simple electrolytic strategy in fluorinated solvents allows the modulation of the substrate’s nucleophilicity and the stabilization of the intermediates as well as of the final product from over-oxidation.1 Introduction2 Solvent Effects in Kolbe Electrolysis and Anodic Fluorination3 Unique Solvent Effects of 1,1,1,3,3,3-Hexafluoropropan-2-ol (HFIP)4 Anodic Dehydrogenative Coupling Reactions with Use of HFIP as the Solvent5 Conclusion
Keywords: C–C coupling; electrochemical fluorination; electrosynthesis; Kolbe electrolysis; N–C coupling; solvent effect; 1,1,1,3,3,3-hexafluoropropan-2-ol